(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
Following the author’s previous studies, this scientific article uses the proof of the “Principle” of Maximum Work (PMW), used in metals plasticity theory and surface tribology, through a more general mathematical framework starting from the fundamental Constructal Law. In this paper, the author focuses on the mathematical proof of convexity and normal rule properties of both plastic and friction flow criteria.